Disability In Schizophrenia and Bipolar Affective Disorder - S., Karthick (International Journal of Psychosocial Rehabilitation, 2017)
Background & Objectives: Schizophrenia and bipolar affective disorders are known for the increased level of disability to the sufferer in various areas to an individual and through that worsen the burden on the caregivers. Although both are chronic illnesses the level of disability may vary. Aim: The present study was undertaken to assess and compare the disability in patients with schizophrenia and bipolar affective disorder (mania). Methodology: The present study was a cross-sectional study conducted at the outpatient department of Central Institute of Psychiatry, Ranchi with a sample size of sixty individuals consisted of thirty participants in schizophrenia and thirty participants in bipolar affective disorder (mania) diagnosed as per ICD-10-DCR criteria. Indian Disability Evaluation Assessment Scale (IDEAS) was used for assessing the disability. Results: The study findings were the majority of the patients with the bipolar affective disorder were from rural areas and schizophrenia was from semi-urban areas. There was significantly more disability in patients with schizophrenia with more than 5 years duration than with 2-5 years duration across all domains of IDEAS except the domain of interpersonal activities. Whereas significantly more disability was found in patients with the bipolar affective disorder with 2-5 years duration than with more than 5 years duration across all domains of IDEAS. Conclusion: Disability in patients with schizophrenia have significantly higher level of disability in all domains than bipolar affective disorder. In order to rehabilitate from disability, along with pharmacotherapy, psychosocial rehabilitation for these patients should become a major component of treatment programme for this population